Heritage cereals : tasty and sustainable? : acceptance and important qualities of heritage cereals - Ekblad, Malin (SLU/Dept. of Urban and Rural Development, 2022)
Heritage cereals, a group of cereals that have not been subjected to modern crop breeding, have been getting attention due to their generally high genetic diversity, traits like high drought and disease tolerance as well as high nutritional values. Knowledge about how consumers relate to heritage cereals in Sweden is limited, and therefore this thesis aims to, firstly, explore acceptance, awareness and preferences among a specific consumer group; students in the agriculture program at the Swedish University of Agricultural Sciences, and, secondly, quality perception in relation to heritage cereals among consumers, bakers and retailers, in a Swedish context. The thesis used a mixed-method approach, and is based on quantitative data from a survey to capture perspectives from the student consumer group and semi-structured interviews with bakers and retailers to gain additional perspectives about food quality. The findings from this study suggests that the awareness of heritage cereals is high among the specific consumer group. Bread and pasta make up the most preferred food products, and supermarkets were the most preferred shopping location. Gender had some influence on differences within the group, while high similarities were found between the different educational backgrounds. Results from the survey indicate that taste and Swedish food production are two very important food quality aspects for heritage cereals. Additionally, quality aspects like health, environmental impact, organic and local production were also found to be important to consumers, bakers and retailers. Consuming heritage cereals can also be seen as a tool to support sustainable food systems and different political discourses, avoiding risks associated with industrial farming and express belonging to certain cultural identities. These were also important dimensions of heritage cereal food quality.